Association Between ABO Blood Type and Risk of Pulmonary Embolism: A Systematic Review and Meta-Analysis - Xujie Wang MD; Xudong Wang MD; Zihan Wang MD (Clinical and Applied Thrombosis/Hemostasis)
Previous studies have identified ABO blood type as a risk factor for venous thromboembolism. However, the association between ABO blood type and pulmonary embolism (PE) has not yet been explored. The PubMed, Cochrane Library, Embase, and Web of Science databases were searched from inception to May 2025. Case–control/cross-sectional and cohort studies focusing on the effect of ABO blood type on PE were evaluated. Nine eligible studies were included for meta-analysis. The pooled risk of PE was 1.45 (95% confidence interval [CI] 1.23-1.72, I 2  = 89.6%) for the non-O group compared with the O group, and there was significant heterogeneity. After the exclusion of two studies that may have produced unstable results, the risk was still significant (Relative Risk [RR] 1.39, 95% CI 1.22-1.59, I 2  = 47.1%), but there was less heterogeneity and improved stability. Both the A (RR 1.29, 95% CI 1.08-1.55, I 2  = 47.1%) and AB (RR 1.41, 95% CI 1.18-1.69, I 2  = 0.0%) blood types conferred an increased risk of PE, whereas the risk for the B group was not significant ( P  = .089). With respect to origin, only studies from America ( P  < .001), but not from Europe ( P  = .064) or Asia ( P  = .102), showed increased PE risk. Regarding study type, the results were significant both in case–control/cross-sectional ( P  < .001) and cohort studies ( P  = .002). In conclusion, individuals in the non-O group were associated with an increased risk of PE compared with those in the O group both in case–control/cross-sectional and cohort studies.